Factors Associated with Fatigue in Chronic Kidney Disease Patients Undergoing Hemodialysis: A Systematic Review - Firman Prastiwi; Titin Andri Wihastuti; Dina Dewi Sartika Lestari Ismail (Jurnal Kedokteran Brawijaya, 2021)
Fatigue is the primary complaint most frequently reported by patients on hemodialysis. The importance of knowing the factors related to fatigue is a strategy that can be carried out by health workers in optimally applying interventions to reduce patient fatigue problems. This systematic review aimed to determine the factors associated with fatigue in patients undergoing hemodialysis. The systematic review method began by identifying research articles in the Pubmed, ProQuest, Ebsco, and ScienceDirect databases in 2011–2020. Review protocol was using PRISMA. Based on the results of the analysis, it was obtained 23 articles that discussed demographic factors, physiological factors, socioeconomic factors, situational factors, and psychological factors that could be associated with fatigue in hemodialysis patients. There is much to learn about fatigue in patients undergoing hemodialysis, including causative factors, assessment of severity, and effective management of fatigue so that it can be used as a benchmark for determining appropriate interventions.